On the Maximal Graph of a Commutative Ring - Masoumeh Soleimani; Fatemeh Mahmudi; Mohammad Hasan Naderi (Mathematics Interdisciplinary Research, 2023)
‎Let $R$ be a commutative ring with nonzero identity‎. ‎Throughout this paper we explore some properties of two certain subgraphs of the maximal graph of $R$‎.